Specific Character of Using English in Phraseology of Radio Communication (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2018)
The article deals with the features of professional communication in the aviation industry and the role of the organization of English language communication during radiotelephony. English is the language for all pilots and air traffic controllers who wish to operate in any international aviation environment. The International Civil Aviation Organization, called ICAO, determines the English language requirements. It has been determined that English has become an integral factor in ensuring the effectiveness of international cooperation and security during air transport. The main factors of misunderstanding between the pilot and the air traffic controller are underlined, the radiotelephony characteristics of civil aviation are identified corresponding to the main principles of aviation communication of encoding information within its limits, namely: concision, clarity, non-ambiguity. English has been chosen as the official language of flight in the United States and continues to be the recommended lingua franca for international use. In some cases, a lack of English proficiency in pilots or controllers has led to disastrous and even fatal catastrophes. While miscommunications between flight crews and air traffic control personnel may have been only one aspect of these incidents and accidents, the lack of ability for all parties involved to understand crucial directions via a common English may have been the most important contributing factor leading to these tragedies. Without agreed upon standards for English proficiency and common phraseology, the aviation industry continues to be at risk for future language-related accidents. Air traffic communications often deviate from standard phraseology in emergency situations towards a more conversational style. English proficiency beyond the basic understanding of aviation phraseology may be necessary. In addition, a cultural awareness of the variety of English spoken in countries encountered during flight may help avoid misunderstandings and miscommunications. Miscommunications may broadly be applied to a range of verbal communications problems ranging from misunderstandings, such as those due to ambiguity, cultural differences, language structure, and so on, to more technical problems. Studies indicate that miscommunication is a pervasive problem in air traffic control and, has been a causal factor in numerous fatal accidents. According to the researches types of miscommunication can be grouped as follows: expectations, code switching and L1 interference problems, paralinguistic factors and lexical ambiguity.
Keywords: plain language; phraseology; radiotelephony; expectations; code switching and L1 interference problems; paralinguistic factors and lexical ambiguity